A Versatile and Robust Platform for the Scalable Manufacture of Biomimetic Nanovaccines. Issue 15 (1st May 2021) - Hu, Hanze; Yang, Chao; Zhang, Fan; Li, Mingqiang; Tu, Zhaoxu; Mu, Lizhong; Dawulieti, Jianati; Lao, Yeh‐Hsing; Xiao, Zixuan; Yan, Huize; Sun, Wen; Shao, Dan; et al.
Abstract: Biomimetic strategies are useful for designing potent vaccines. Decorating a nanoparticulate adjuvant with cell membrane fragments as the antigen‐presenting source exemplifies, such as a promising strategy. For translation, a standardizable, consistent, and scalable approach for coating nanoadjuvant with the cell membrane is important. Here a turbulent mixing and self‐assembly method called flash nanocomplexation (FNC) for producing cell membrane‐coated nanovaccines in a scalable manner is demonstrated. The broad applicability of this FNC technique compared with bulk‐sonication by using ten different core materials and multiple cell membrane types is shown. FNC‐produced biomimetic nanoparticles have promising colloidal stability and narrow particle polydispersity, indicating an equal or more homogeneous coating compared to the bulk‐sonication method. The potency of a nanovaccine comprised of B16‐F10 cancer cell membrane decorating mesoporous silica nanoparticles loaded with the adjuvant CpG is then demonstrated. The FNC‐fabricated nanovaccines when combined with anti‐CTLA‐4 show potency in lymph node targeting, DC antigen presentation, and T cell immune activation, leading to prophylactic and therapeutic efficacy in a melanoma mouse model. This study advances the design of a biomimetic nanovaccine enabled by a robust and versatile nanomanufacturing technique. Abstract : Flash nanocomplexation (FNC) is exploited to produce cell membrane‐biomimetic nanotherapeutics in a robust, versatile, reproducible, and scalable manner. Cancer cell membrane‐coated, CpG‐loaded mesoporous silica nanoparticles fabricated using FNC exhibit better lymph node targeting, T‐cell activation, anticancer immunoresponse, and combined immunotherapeutic outcome than sonication‐produced counterparts.